Comparative criminal justice - Pakes, Francis J. (Routledge, 2019)
Cover; Half Title; Title Page; Copyright Page; Table of Contents; List of Tables; 1 Comparative criminal justice: better knowledge, better justice?; The utility of the comparative project; The nature of this book; Further reading; Study questions; 2 Conducting comparative research in a globalised world: the aims of comparison; Research orientations; Doing comparative research; Case studies; Focused comparisons; Statistical analysis; Using criminal justice statistics comparatively; Comparative criminal justice and globalisation; Methodological hazards; Conclusion: a cosmopolitan turn?